Synthesis and characterization of a new reusable calix[4]arene-bonded silica gel sorbent for antidiabetic drugs. Issue 39 (5th September 2022) - Hokmabadi, Fahimeh; Zadmard, Reza; Jalali, Mohammad Reza; Abaee, M. Saeed
Abstract : C4BS is a new reusable calix[4]arene-bonded silica gel adsorbent for dapagliflozin (DAPA), empagliflozin (EMPA) and linagliptin (LINA) as antidiabetic drugs. Abstract : A novel calix[4]arene-bonded silica gel (C4BS ) is prepared by covalent attachment of a calix[4]arene derivative to silica gel through a thiol–ene process. The structure and properties of C4BS were studied by Fourier Transform Infra-Red (FTIR) spectroscopy, thermal gravimetric analysis (TGA), elemental analysis (CHN), scanning electron microscopy (SEM), and surface area analysis (BET). In addition, the binding affinity of some antidiabetic drugs towards C4BS was investigated, by quantitative measurement of the drugs in aqueous solution using UV-visible spectroscopy. Results showed that C4BS has higher affinities than plain silica gel for binding to empagliflozin, dapagliflozin and linagliptin at neutral pH, while metformin hydrochloride was not adsorbed efficiently using either C4BS or plain silica gel. Thus, C4BS can be introduced as a promising binder for selective adsorption of the quoted antidiabetic drugs in pharmaceutical effluents, while being reusable by aqueous/acetonitrile (1 : 1) extraction.